The Effect of Project Based Blended Learning on Visual Literacy Skills - Subastian, Eko; Nursalim, Moch.; Bachri, Bachtiar S. (Journal of Ecohumanism, 2024)
The goal of this study is to determine the test’s outcomes, including the effects of learning motivation, direct instruction, and the project-based learning model on the learning outcomes for visual literacy skills. A 2x2 factorial design was used in this experimental study. This study’s subject is the eighth grade at SMPN 13 Samarinda City, which consists of four 120-student classes. The experiment’s target subjects are selected using classical randomization, which consists of four classes. The Analysis of Variant (Anova) statistical test was utilized to assess the study’s hypothesis. The computation’s outcomes demonstrate that: In light of the analysis’s findings in this study, The utilization of the Project Based Learning Model and the direct instruction approach has a substantial impact on the learning outcomes for the Visual Literacy Skill. The F calculation of 151,261 with sig = 0.000 < 0.05 illustrates this. This indicates that (1) the adoption of the Project Based Learning Model and the direct instruction technique has an impact on the learning outcomes of visual literacy skill, and (2) learning motivation has no impact on those same learning outcomes. The goal of F = 16,149 with sig = 0.000 > 0.05 demonstrates this. This indicates that learning motivation has no effect on the outcomes of learning visual literacy skills, and that the usage of the PBBL model, direct instruction, and gender do not interact to affect these outcomes. F calculates =14,351 with sig = 0.000 > 0.05. This indicates that the learning model’s ability to affect the learning outcomes for visual literacy skills is independent of learning motivation.